Unusual Closed Traumatic Avulsion of Both Flexor Tendons in Zones 1 and 3 of the Little Finger - Marie-Aimée Päivi Soro; Thierry Christen; Sébastien Durand (Case Reports in Orthopedics, 2016)
Closed tendon avulsion of both flexor tendons in the same finger is an extremely rare condition. We encountered the case of a patient who presented a rupture of the flexor digitorum profundus in zone 1 and flexor digitorum superficialis in zone 3 in the little finger. This occurrence has not been reported previously. We hereby present our case, make a review of the literature of avulsion of both flexor tendons of the same finger, and propose a treatment according to the site of the ruptures.